Sistema gráfico interativo para análise de nucleação e propagação detrincas - Leandro Lopes da Silva (2016)
This masters thesis is concerned about computational implementation of an interactive graphical software that integrates pre-processor, constitutive models, nonlinear equation solvers and post-processor for analysis of nucleation and propagation of cracks in two-dimensional domain in quasi-brittle medium. The physically nonlinear analysis begins using the Standard Finite Element Method (FEM), through which the initial medium de gradation is simulated in a distributed manner employing constitutive methods based on elastic degradation. The threshold stage of cracks nucleation is indicated by singularity of the acoustic tensor, that brings us to the classical strain localization condition. The presence of cracks is simulated through kinematic method that incorporates the discontinuities by using enriched interpolationsbasedonthe Generalized Finite Element Method (GFEM), whereas the cracks propagation is also indicated by singularity of the acoustic tensor. The relationship between stresses and displacements in the crack path is based on cohesive forces acting on the crack plane. This combination of constitutive and kinematic methods has the advantage of not having to pre-set crack path or redene the mesh duringprocessing. At the end of the analysis, the nucleation phenomenon and the effects of the presence of cracks and their propagation can be viewed using the post-processor module tools. The implementations were performed on the INSANE (INteractive Structural ANalysis Environment) platform.